Murottal Murottal Qur’an stimulation as Evidance Based Nursing to increase critical patient awareness in Intensive Care Units: Murottal Qur’an stimulation as Evidance Based Nursing to increase critical patient awareness in Intensive Care Units: Stimulasi murottal Qur’an sebagai Evidance Based Nursing untuk meningkatkan kesadaran pasien kritis di Intensive Care Unit - Ari Kurniawan (Caring : Jurnal Keperawatan, 2021)
Critical patients who have decreased consciousness require immediate treatment and treatment to reduce pain and prevent death. The purpose of implementing Evidance Based Nursing is to increase the level of awareness in critical patients using murottal Qur’an stimulation. The application of Evidance Based Nursing to 8 people, the sample was selected by purposive method based on predetermined criteria. Murottal Qur’an stimulation using headphones is done once a day for 30 minutes for 3 consecutive days. Murottal Qur’an stimulation using the Surah Ar-Rahman, every day an evaluation after the intervention. Of the 8 samples that performed murottal Qur’an stimulation, 7 samples experienced increased awareness. Murottal stimulation The Qur'an can stimulate the activation of dopamine which physiologically plays a role in increasing one's alertness decreases the tension of the autonomic nervous system that repairs and renews brain nerve tissue, simulation as a neuro protector is to save tissue affected by ischemia, limit infarcted areas so as not to expand, and minimize reperfusion injury, so as to increase the level of awareness of critical patients. Murottal Quran stimulation can increase the level of awareness, so this action can be applied to critical patients who have decreased consciousness. Pasien kritis yang mengalami penurunan kesadaran memerlukan perawatan dan penanganan segera untuk mengurangi kesakitan dan mencegah kematian. Tujuan penerapan Evidance Based Nursing ini adalah untuk meningkatkan tingkat kesadaran pada pasien kritis dengan menggunakan stimulasi murottal Qur’an. Penerapan Evidance Based Nursing pada 8 orang, sampel dipilih dengan cara purposive berdasarkan dengan kriteria yang telah ditetapkan. Stimulasi murottal Qur’an menggunkan headphone dilakukan sehari sekali dengan waktu 30 menit selama 3 hari berturut-turut. Stimulasi murottal Qur’an menggunakan surah Ar-rahman, setiap hari dilakukan evaluasi setelah intervensi. Dari 8 sampel yang dilakukan stimulasi murottal Qur’an, 7 sampel mengalami peningkatan kesadaran. Stimulasi murottal Qur’an dapat menstimulasi pengaktifan dopamin yang secara fisiologis berperan dalam meningkatkan kewaspadaan seseorang menurunkan ketegangan sistem saraf otonom yang memperbaiki dan memperbaharui jaringan saraf otak, simulasi sebagai neuro protektor adalah menyelematkan jaringan yang terkena iskemia, membatasi area yang infark agar tidak meluas, dan meminimalisir cedera reperfusi, sehingga dapat meningkatkan tingkat kesadaran pasien kritis. Stimulasi murottal Quran mampu meningkatkan tingkat kesadaran, sehingga tindakan ini dapat diterapkan pada pasien kritis yang mengalami penurunan kesadaran.